The Latin Language and Medical Terminology: Test Tasks for Independent Work for the First-Year Students of the Medical Faculties with the English Medium of Instruction, Speciality 222 “General Medicine” - Kulichenko, Alla; Titiyevska, Tetiana; Куліченко, Алла Костянтинівна; Тітієвська, Тетяна Василівна (Запорізький державний медичний університет, 2020)
Test tasks are made up for the first-year students of the medical faculties with the English medium of instruction, speciality 222 “General Medicine”. Test tasks contain specialized design-structure tasks for independent work. The purpose of test tasks is to revise the material learnt during Latin classes and to prepare for assessment and credit in the Latin language and medical terminology.